The Impact of Transjakarta Bus Rapid Transit (BRT) Operationalization on Economic Growth and Unemployment Rate in DKI Jakarta Province - Rico Bagus Satrio; Achmad Kemal Hidayat; Amelia Hayati (PT Mattawang Mediatama Solution, 2023)
Special Capital District Jakarta province is one of the most populous cities in Indonesia. People commute every day mostly by using private vehicles to meet their needs. Somehow another alternative comes as one of the longest lengths of BRT track in the world, operationalization of the Transjakarta BRT is expected to be able to contribute to economic growth and improve people's accessibility so that it could reduce the unemployment rate. This paper aims to determine the magnitude of BRT operationalization on economic growth and the unemployment rate in Jakarta. This paper used panel data consisting of 5 cities in Jakarta during 2016-2021. 2 Stage Least Square is being used as a methodology that estimates endogenous & predetermined variables. Secondary data used consist of economic growth, the unemployment rate as the endogenous and BRT kilometer traveled private vehicle units, stock capital growth, and the number of the labor force as the predetermined ones. The findings in this study indicate that the operationalization of BRT contributes 0,01577231 to economic growth and decreases 0,00120415 the employment rate in Jakarta at the significance level of 5% ceteris paribus. It suggests that in the long-run BRT, operationalization plays an important role in the transportation economic sector in Jakarta